Liposarcoma in the thoracic wall. Case study. - Julio Sarmiento Sánchez; Lidia Torres Aja; Dorys González Díaz (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2008)
Presentation of the case of a white male (86 years old) referring to have being operated one year ago due to a tumor in his back which has being enlarging in the last six months including not fetid suppuration in the last month. The physical examination showed a big ulcerated tumor of about 20 cm of diameter with yellow secretion. It turned to be a lymphosarcoma grade II, with wide necroses zones, diameter of 20x14x7 cm and weighing 746grs. This is a very infrequent case, the only one reported in our province.